Detecção de Pseudomonas aeruginosa e staphylococcus aureus na mucosite oral em pacientes leucêmicos submetidos ao tratamento antineoplásico - Goeritz, Ana Cláudia Nunes Duarte (2017)
Neoplastic diseases are an important reality in modern society, displaying high incidence in Brazil and over the world. Acute lymphocytic leukemia is the most common cancer in children, and is characterized by the elevated and disordered production of immature leukocytes in the bone marrow. The oral complications resulting from the therapy used to treat leukemia occur quite frequently. Mucositis is one such example, and is characterized by irritation of the oral mucosa, being the most common manifestation of direct stomatoxicity, and presenting diffuse ulceration of the non-keratinized buccal mucosa. The objective of this study was to detect the possible association between Pseudomonas aeruginosa and Staphylococcus aureus and the development of oral mucositis in patients receiving antineoplastic treatment by use of the PCR technique. To this end, 46 Acute Lymphocytic Leukemia (ALL) patients who were being treated at HEMOAM in the city of Manaus were interviewed and examined. A questionnaire created specially for this study was used, in order to facilitate the collection of data including age, sex, clinical features, and oral health condition. Saliva was collected by sterile swab before the start of chemotherapy, and 14 days after the treatment. During chemotherapy, nausea, vomiting and fever were the most commonly reported manifestations, besides mucositis and gingival bleeding. Conventional PCR revealed the presence of Pseudomonas aeruginosa and Staphylococcus aureus in all treament phases, and that S. aureus was present in 79% of mucositis subjects. Based on the statistical analysis, the presence of P. aeruginosa was positively related with lower haemoglobin levels after chemotherapy, while S. aureus was intimately associated with mucositis, nausea, fever, diet type, and previous dental intervention. Whilst this bacteria has shown positive association with many clinical parameters, additional studies must be performed to assess its potential pathogenic role in oral mucositis. In view of the results, it can be suggested that myelosuppression induced by chemotherapy favors the developent of oral mucositis and the proliferation of potential pathogenic species, especially Staphylococcus aureus